A low-cost and autonomous tracking device for Alzheimer's patients. Issue 4 (9th December 2019) - Hegde, Niharika; Muralidhara, Shishir; Ashoka, D.V.
Abstract : Purpose: Alzheimer's is the most commonly occurring neurodegenerative disease and progressive cognitive impairment is its major symptom due to which the patients tend to wander and get lost in unfamiliar places. This is a constant cause of worry for caretakers and a source of distress to the patients themselves. The paper aims to discuss this issue. Design/methodology/approach: This paper presents a low-cost, autonomous, embedded systems-based wearable device for real-time location tracking using GPS and the concept of geo-fencing. The system provides real-time updates in the form of a text message sent to the mobile number of a family member or caregiver. Findings: An alert is sent whenever the patient moves out of a certain "safe zone" area and sends subsequent updates after every 5 min of such an event. The system supports caregivers of patients with early and moderate Alzheimer's disease. Social implications: Alzheimer's patients are prone to disorientation, confusion and tend to wander off. Since the device eliminates the need for the patients to operate it and is instead at the discretion of the system itself, the chances of it failing to help are minimized. Hence, with this project, the authors address the need for an autonomous device that can assist caretakers in tracking Alzheimer's patients. Originality/value: The various existing technologies that are in use now for tracking are often high in price, not tailored to Alzheimer's and are non-autonomous. To overcome this, the authors utilized easily accessible technology into developing this system, which not only be affordable, but also addresses the major flaw in existing systems – which is that they rely on being operated by the patients themselves.